Silicon spraying alleviates calcium deficiency in tomato plants, but Ca-EDTA is toxic - de Souza Alonso, Tales Arthur [UNESP]; Ferreira Barreto, Rafael [UNESP]; de Mello Prado, Renato [UNESP]; Pereira de Souza, Jonas [UNESP]; Falleiros Carvalho, Rogério [UNESP] (Wiley, 2020)
Background: The occurrence of calcium (Ca)-related disorders is common in tomato production and may be due to factors such as excess nitrogen (N) fertilization. Thus, Ca sprays are often applied as preventive measure to avoid the occurrence of blossom-end rot. In addition, evidence indicates that Si can act beneficially on tomatoes and relieve Ca deficiency. Aims: We aimed to verify the effects of Ca-EDTA and Si application on tomatoes experiencing moderate Ca deficiency. Methods: Tomato plants were grown in nutrient solutions with Ca sufficiency (+CaR) or Ca deficiency (–CaR) or under conditions of –CaR plus 25 mM Ca-EDTA shoot sprays (–CaR +CaS), –CaR plus 7.1 mM Si shoot sprays (–CaR +SiS) or –CaR +CaSiS, with a total of nineteen sprays being supplied after anthesis, per foliar treatment. Results: Plants grown under –CaR had smaller leaves and fruits, and new shoots were deformed. Plants that were sprayed with Ca-EDTA and Ca-EDTA plus Si in the same solution developed more blossoms than those grown without Ca; however, they showed chlorosis and necrosis on the edges of older leaves, i.e., Ca-EDTA was toxic. However, the plants sprayed with Si alone were the most similar to control plants, showing only deformations in the younger leaves. Conclusion: Ca-EDTA at 25 mM sprayed twice a week after anthesis, totaling 19 sprays, caused toxicity in MT tomatoes. Sodium silicate (7.1 mM Si) sprayed twice a week after anthesis, totaling 19 sprays, made MT tomatoes less sensitive to Ca deficiency. Thus, we highlighted the potential of Si spraying to alleviate the slight Ca deficiency, which is relatively common in horticulture.
Keywords: beneficial elements; blossom-end rot (BER); chelate; ethylenediaminetetraacetic acid; Solanum lycopersicum